Época de colheita, irrigação, fitoquímica e atividades carrapaticida e fungicida do óleo essencial de genótipos de Lippia gracilis Schauer - Cruz, Elizangela Mércia de Oliveira (2013)
The aim of this study was to determine the influence of harvesting time and water stress on the chemical composition of the essential oil and to test the activities against ticks and fungus of the essential oil of L. gracilis. For the analysis of harvest season the plant material was collected from seven genotypes of L. gracilis at the Research Farm "Campus Rural da UFS", in the rainy and dry seasons. The experiment testing water stress was conducted in the dry season. The extraction of essential oils was performed in the Laboratory of Phytotechnology of the UFS through hydrodistillation. Chemical analysis of the essential oil performed using GC-MS in the Laboratory of Chromatography of the UFS. For the activity tests against ticks package larvae and immersion of engorged tick Rhipicephalus microplus in different concentrations of essential oil, thymol or carvacrol. To test of fungicidal activity, the essential oil at different concentrations was added to PDA medium. Each plate was inoculated with mycelia culture of Thielaviopis paradoxa. The essential oil of L. gracilis presented two distinct chemotypes, one genotype LGRA-106 presenting as major compound thymol and the other genotypes presenting carvacrol as major compound. The leaves provided essential oil with an average grade of 1.55% in the rainy season and 2.09% in the dry season. In the rainy season there was no significant difference in both the yield and the content. The chemical composition of essential oils L. gracilis showed high levels of terpenes, 92% in the rainy season and 96% in the dry season. In the experiment with irrigation the values of content and yield of all genotypes were smaller when compared without irrigation. In general, the species L. gracilis, for the presence of water in the soil, provides stability in the chemical composition of the essential oil regardless of season, since plants subjected to irrigation, even in the dry season, the essential oil produced in quantity and quality similar to the rainy season. The essential oil of L. gracilis exhibits high activity against ticks, proven by lethal concentrations of genotypes LGRA-201 (1.31 mg.mL-1) and LGRA-106 (4.66 mg.mL-1), demonstrating efficiency in the control of this parasite. The tests showed that the concentrations 0.45; 0.91 and 2.75 mg.mL-1 of all genotypes of L. gracilis completely inhibited the development of the pathogen T. paradoxa, corresponding to a percentage of mycelium growth inhibition of 100%. The concentration of 0.18 mg.mL-1 of essential oil was sufficient to significantly reduce the number of spores of T. paradoxa. The minimal fungicidal concentration T. paradoxa was found between concentrations from 0.80 to 0.98 mg.mL-1 for the essential oils and 0.26 mg.mL-1 for carvacrol and 0.35 mg.mL-1 to thymol.